The role of madrasah-based management in improving the quality of education: Case studies at Tasikmalaya madrasahs - Tauhid, Asep Budi (UIN Sunan Gunung Djati Bandung, 2025)
Improving the quality of madrasah education is a strategic imperative in addressing the challenges of educational relevance, efficiency, and equity within Indonesia’s decentralized education system. This study aims to analyze the role of Madrasah-Based Management (MBM) in enhancing educational quality through case studies at three state madrasahs in Tasikmalaya Regency: Madrasah Tsanawiyah (MTs—Islamic Junior High School) Negeri Pamoyanan, MTs Negeri Singaparna, and MTs Negeri Sukamanah. Using a qualitative approach and case study method, data were collected through in-depth interviews, participatory observation, and document analysis, and examined using Miles and Huberman’s interactive analysis model. The findings reveal that the effectiveness of MBM is largely determined by transformational leadership, teacher capacity-building through continuous professional development, and active community involvement in educational decision-making. Among the three institutions, MTs Negeri Sukamanah demonstrates a more structured and responsive managerial approach, while MTs Pamoyanan and MTs Singaparna still struggle with financial limitations, insufficient human resources, and low public engagement. The study highlights that MBM is not merely an administrative model but a transformative strategy that requires the synergy of institutional autonomy, supportive policies, and meaningful partnerships with local communities. As a policy contribution, this research recommends strengthening madrasah leadership training, aligning curricula with local values, increasing performance-based funding, and expanding public education literacy as key foundations for sustainable quality improvement in Indonesia's madrasah system.